The Impact of a Modified Version of the Olympic Values Education Programme in Student-Athletes of Puerto Rico - Ramirez Rodriguez, Coral Marie (Πανεπιστήμιο Πελοποννήσου, 2021)
The present investigation explores the effects of a modified Olympic Values Education Programme, particularly in the knowledge and moral competence of student-athletes of Puerto Rico. The participants of this study were student-athletes of the Albergue Olímpico Baseball Academy (AOBA) (n=111), from 6th to 11th grade. Participants were given a questionnaire as a pre-test and then attended an Olympic Values Education Programme designed for the Puerto Rican population. After the intervention that consisted of 10 sessions, they were given the same questionnaire as a post-test. The results from the pre-test and post-test were analyzed to determine if the intervention is an effective educational tool. The findings say that, even though there were differences between the pre and post-test, the differences are not statistically significant. Additionally, results revealed that the educational class significantly affects ones’ morality in the framework of sport. By adapting a modified version of an Olympic Values Education Programme like OVEPUR, we can conclude that we could improve ones’ knowledge, ideas, attitudes, and perception concerning Olympism. We could, of course, improve ones’ moral competence and judgment. Nevertheless, a longer intervention duration may be necessary as well as being delivered in a physical education setting. This study can be used as a base for future investigation in this population and regarding the topic of moral development and Olympic education, whether in student-athletes or teachers and coaches.
Keywords: Olympic education - Curriculum - Puerto Rico; Olympism; Physical education and training - Curriculum - Puerto Rico; Physical education and training - Study and teaching (Elementary) - Puerto Rico; Olympic movement; Olympics - Social aspects; Ολυμπιακή παιδεία - Πρόγραμμα μαθημάτων - Πουέρτο Ρίκο; Ολυμπισμός; Φυσική αγωγή και εκπαίδευση - Πρόγραμμα μαθημάτων - Πουέρτο Ρίκο; Φυσική αγωγή και εκπαίδευση - Μελέτη και διδασκαλία (Πρωτοβάθμια) - Πουέρτο Ρίκο; Ολυμπιακό κίνημα; Ολυμπιακοί αγώνες - Κοινωνικές απόψεις; Olympic education; Moral competence; OVEP; Sports settings; Students-athletes